Pengaruh Workload Terhadap Kinerja Air Traffic Controller di Perum LPPNPI Cabang Pembantu Tanjung Pandan - Dwi Lestary; Amanda Yessy Novantika; Djoko Jatmoko; Imam Sonhaji (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The Perum LPPNPI Tanjung Pandan Sub-branch lacks personnel, but the strategic location of the airport causes many small planes to refuel, which affects the increase in traffic. This, of course, causes the workload to increase as well. The Controller's service schedule is not in accordance with PM No. 166 of 2020. This study aims to find out how much influence workload has on the performance of air traffic controllers at Perum LPPNPI Tanjung Pandan Sub-Branch. The research method used is a quantitative method with a descriptive approach. Collecting data using a questionnaire survey and documentation study. Data were analyzed with validity, reliability, normality, correlation, and simple linear regression tests. The research instrument used was the NASA TLX method, and with a result of 90.62%, it was concluded that the category of workload level and ATC performance at Perum LPPNPI Tanjung Pandan Sub-branch was classified as very high. The results showed that the workload had a strong and significant influence on ATC performance.